(untitled) (Annals of Bangladesh Agriculture, 2021)
An experiment was conducted at the experimental field of Horticulture Department, Sylhet Agricultural University, Bangladesh during winter season of 2013-2014 to evaluate growth and yield of sweet pepper varieties under net protected condition. The two-factor experiment was laid out in Randomized Complete Block Design with three replications. Three popular sweet pepper varieties viz. BARI Mistimorich-1, California Wonder and Yolo Wonder were grown under three protected systems viz. fine net (120 mesh), coarse net (40 mesh) and open field. Considering the effect of varieties, the highest value for all the parameters viz. fruit length (10.01 cm), fruit diameter (5.90 cm), number of fruits/plant (13.61), fruit yield per plant (0.77 kg), fruit yield (21.31 t/ha) were found in California Wonder followed by BARI Mistimorich-1 and Yolo Wonder. Again, considering the effect of net protection system, maximum values for parameters viz. early flowering, fruit length (10.58 cm), fruit diameter (6.29 cm), number of fruits/ plant (16.14), fruit yield/plant (0.94 kg) and per hectare (26.86 t/ha) were recorded under fine net protection system. Under fine net covering plants produced better quality fruit than open field condition. The earliest flowering (60.67 days), the highest number of fruits per plant (19.18) and the maximum fruit yield (35.71 t/ha) were observed in BARI Mistimorich-1grown under fine net system followed by California Wonder grown under coarse net protected system. Benefit cost ratio (BCR) for fine net (5.28) and coarse net (6.75) protected system were much higher than that of open field (1.64) condition indicating bright future for sweet pepper cultivation under net protected system. Ann. Bangladesh Agric. (2020) 24(2) : 85-94